Communication From The Payment Systems Policy Department of Bank Indonesia Regarding The Implementation Of QRIS Use Among SMES - Ika Atikah; Siti Khumayah; Dedet Erawati (Jurnal Ilmu Komunikasi dan Media Kontemporer, 2026)
Bank Indonesia introduced the Quick Response Code Indonesian Standard (QRIS) as the national standard for QR code based payments. The purpose of this study is to analyze the communication process related to QRIS policy by the Payment System Policy Department. This study employs a qualitative approach using a case study method, which involves in depth interviews and observation. This approach was chosen to enable the researcher to analyze the communication process regarding Bank Indonesia’s policies among MSME stakeholders based on Lasswell’s 1948 communication theory, formulated through the simple question: “Who says what through which channel to whom with what effect?” The research results indicate that the Payment System Policy Department’s communication regarding QRIS is conducted both directly and indirectly, with complementary communication channels involving various stakeholder interests. This suggests that the communication process is collective in nature; however, there are barriers encountered in the field among MSME operators, namely the habit of cash transactions and the absence of incoming payment balances, which create doubts among QRIS users. This study demonstrates that QRIS policy communication does not solely depend on the quality of QRIS implementation; rather, stronger synergy is needed between communication strategies, system technical aspects, and ongoing support to ensure that QRIS adoption proceeds evenly.